Design, build and test IIUM remote controlled glider - Omar, Ashraf Ali; Abd Rihem, Mohd Hafizuddin; Mohamad Hashim, Abdul Rahman; Saiful Bahri, Hani Maisara; Mohamed Noor, Marissa; Ahsanah, Ahmad Najmuddin; Mahmud Zuhudi, Nurul Farahana; Joari, Iqbal; Yazid, Ahmad Shahir (2010)
The main objective of this subject is to design and build a sailplane that meets certain performance requirement. Simple mission profile was used which is include warm up, taxi, takeoff, climb, cruise and landing. The cruising altitude, range and sailplanes requirements and specification has been decided base on certain criteria. The take off weight of the sailplane has been successfully estimated as 1.225 kg. NACA 4412 airfoil was used for the wing sectiion. The fuselage diensions were estimated. The length of the fuselage from nose to tail is 0.8 meter, and the fuselage cross section will be rectangular in shape. The power available was estimated as 0.2 hp. The static stability analysis shows good results since all three components which are wing fuselage and tail gives desirable stability results. After 13 weeks of hard work, the team had managed to complete the fabrication of sailplane and also had managed to have it flown by a hired RC pilot. The aircraft flew without any difficulty and the objectives was reached, which is to perform an unpowered gliding.